Maximal oxygen uptake validation in children with expiratory flow limitation - Robben, Katherine E.; Poole, David C.; Harms, Craig A. (My University, 2013)
A two-test protocol (incremental/ramp (IWT) + supramaximal constant-load (CWR)) to affirm max and obviate reliance on secondary criteria has only been validated in highly fit children. In girls (n = 15) and boys (n = 12) with a wide range of VO[subscript 2]max (17–47 ml/kg/min), we hypothesized that this procedure would evince a VO[subscript 2]-WR plateau and unambiguous VO[subscript 2]max even in the presence of expiratory flow limitation (EFL). A plateau in the VO[subscript 2]-work rate relationship occurred in 75% of subjects irrespective of EFL There was a range in RER at max exercise for girls (0.97–1.14; mean 1.06 ± 0.04) and boys (0.98–1.09; mean 1.03 ± 0.03) such that 3/15 girls and 2/12 boys did not achieve the criterion RER. Moreover, in girls with RER > 1.0 it would have been possible to achieve this criterion at 78% VO[subscript 2]max. Boys achieved 92% VO[subscript 2]max at RER = 1.0. This was true also for HRmax where 8/15 girls’ and 6/12 boys’ VO[subscript 2]max would have been rejected based on HRmax being < 90% of age-predicted HRmax. In those who achieved the HRmax criterion, it represented a VO[subscript 2] of 86% (girls) and 87% (boys) VO[subscript 2]max. We conclude that this two-test protocol confirms VO[subscript 2]max in children across a threefold range of VO[subscript 2]max irrespective of EFL and circumvents reliance on secondary criteria.
Keywords: VO2max; Expiratory flow limitation; Oxygen uptake; Children